Embryonic Stem Cells Overexpressing the Recognition Molecules L1 and Tenascin-R Enhance Regeneration in Mouse Models of Acute and Chronic Neurological Disorders - Hargus, Gunnar; Bernreuther, Christian (IntechOpen, 2011)
None